Activity Budget and Behavioral Repertoire of Mysore Slender Loris Loris lydekkerianus lydekkerianus in Keelaveliyur, Tamil Nadu, India - Lavanya, Ravichandran; Gokula, Varadharajan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Animal, to survive and reproduce, exhibits different types of behaviors and thus studying behavior is vital to fully understand the animal. In the present study, an attempt was made to study the behaviors and activity budget of Mysore slender loris Loris lydekkerianus lydekkerianus in Keelaveliyur, Tamil Nadu, India. In total, 1284 hours of observation were made on 46 lorises (16 adult males, 12 adult females, five sub-adult males, five sub-adult females, and eight infants) from Jan 2017-Jan 2018. Mysore slender lorises were nocturnal in the habit at Keelaveliyur, Tamil Nadu. Lorises awoke between 17:00 h and 18:00 h and ceased their activities between 07:00h and 08:00h. They were almost inactive between 07:00h to 17:00h. A total of 15 different categories, comprising 45 different behaviors were cataloged for the Mysore slender loris.